Semi-vertebral column resection with preservation of posterior ligament complex for Kümmell’s disease: a case report - Tong-Hao Wang; Zhi Liu; Yong-Gang Tian; Guo-Yue Yang; Li-Qiang Han (Journal of Medical Case Reports)
Abstract Background Kümmell’s disease is characterized by ischemic osteonecrosis and nonunion after osteoporotic vertebral compression fractures, leading to intractable low back pain, pseudoarthrosis, kyphosis, and neurological dysfunction, which can seriously affect the quality of life and life expectancy of patients. Although many surgical methods have been reported, uniform standard procedures for Kümmell’s disease are still lacking. Case presentation This case described a new procedure for Kümmell’s disease. A 67-year-old woman from China underwent semi-vertebral column resection through the posterior of the diseased vertebra, while the posterior ligament complex and the contralateral spinal structure were preserved. Subsequently, intervertebral titanium cage support bone graft fusion combined with posterior pedicle screw internal fixation was conducted, and the patient was followed up with for 22 months. Kyphosis Cobb angle was 20° 2 weeks post-surgery and was maintained at 20° even after 22 months. Titanium cage was in a good position 2 weeks and 22 months after surgery. Conclusion This new spine surgery could completely decompress the spinal canal and reduce the iatrogenic destruction of spinal stability, which might be helpful for the reconstruction and maintenance of spinal stability.